Formulation and Evaluation of Antioxidant Peel-Off Mask Ethanol Extract Sarang Semut (Myrmecodia sp.) Using DPPH 2,2-Diphenyl-1-picrylhydrazyl Method - Ayuningtyas, Nurista Dida; Febrianto, Yahya; Prasetyo, Alno (Universitas Negeri Semarang, 2021)
Background: Myrmecodia sp extract is known to be effective as an antioxidant on a concentration of 5-50 ppm. Antioxidants are substances that can scavenge free radicals. Free radicals can cause skin damage. Peel off mask is a cosmetic product that function as a dead skin peel mechanically containing synthetic polymers that are quite safe and effective. Aim: The purpose of this study was to determine the antioxidant effectiveness of the Myrmecodia sp extract. Method: The research used variations in the Myrmecodia sp extract of 2 %, 3%, and 4 %. The evaluation was carried out on the physical properties of the peel off mask and the antioxidant activity test. The antioxidant activity test used the 2,2-Diphenyl-1-picrylhydrazyl method. Statistical tests were carried out on the physical properties of the preparation and IC50 peel off mask using the one-way ANOVA test with a 95% confidence level. Result: Based on this research, it was found that the gel peel-off mask preparation of Myrmecodia sp. extracts has organoleptic of a bit thick, brown and odourless. The value of adhesion is between 10.33-13.04 seconds, pH 6.27-6.75, viscosity 17.00-22.67 dPas, and drying time 17.33-24.33 minutes. The test for the antioxidant activity of IC50 peel off mask at F 2, F 3 and F 4 was 49.4 ppm, 39.41 ppm and 35.25 ppm respectively. Conclusion: The peel-off gel mask of Myrmecodia sp. extracts has the potential as an antioxidant with the strong ability category.